Optimistic Christian Verticals and Destructive Secular Horizontals in Joachim Ringelnatz’s and Ödön von Horváth’s Experimental Fairy Tales - Duleba, Maxim (Respectus Philologicus, 2023)
This article contributes to the discourse on experimental interwar fairy tales as a subgenre that undermines the anachronistic fairy-tale conventions to a selective negation or recontextualization in accordance with a contemporaneous cultural crisis. The contribution consists of demonstrating how fairy tales provide popular interwar religious authors with a platform to parallel the critical mirroring of their secular contemporaneous society with an articulation of a Christian, humanist optimism. A spatially focused comparison of Ödön von Horváth’s cycle of fairy tales Sportmärchen (1924–1926, published posthumously in 1972), and Joachim Ringelnatz’s Nervosipopel: Elf Angelegenheiten (1924) distinguishes the vertical and horizontal textual spaces to demonstrate that both authors reflect their metaphysically uprooted society through a negation of the genre's characteristic orientation toward harmonic equilibriums on a horizontal spatial axis. However, by overlaying destructive horizontals with antinomic, transcendence-signifying Christian verticals, the tales also articulate a modality of nearness to God, even in the secular world. This symbolic and positive vertical motion correlates with preserving the genre's characteristic idealization of a child.
Keywords: Ödön von Horváth; Sportmärchen; Joachim Ringelnatz; interwar fairy tales; fairy-tale spatiality